Evaluation of a Streamlined Model of Care for Minor Burn Patients - Finlay, V.; Hendrie, Delia; Allison, Garry; Phillips, M.; Wood, Fiona; Edgar, D. (Lippincott Williams & Wilkins, Inc., 2014)
Minor burns represent the majority of all burn patients in developed countries, yet little information regarding their outcomes is available in the literature. Minor burns at Royal Perth Hospital are provided routine outpatient clinic follow-up at 1 month postinjury resulting in increased ambulatory care demand and inefficiency due to high failure to attend rates. The authors hypothesized that improving patient education and using a posted quality-of-life survey in place of a 1-month outpatient clinic follow-up visit for minor burn patients would improve efficiency without compromising outcome compared to current standard practice. A sample of conservatively managed minor burn outpatients who healed within 14 days were administered a burn care education manual and discharged. Participants were assessed using postal Burn-Specific Health Scale-Brief and satisfaction surveys at 1 month postburn. Their responses were compared to those of patients who had received standard care. The intervention group had a higher, but not statistically significant, median BSHS-B score (156) than the comparison group (153) (P =.05). The intervention group also reported high levels of satisfaction with service. The new model of care is an appropriate strategy for management of minor burn. Its benefit over current hospital-based follow-up is that it saves one clinic appointment, improves efficiency related to nonattendance, and reduces patient burden.